Selection of fungi of the genus Aspergillus phytase for inclusion in animal feed - BIONI, LUCILO BIONI DA FONSECA FILHO; Nascimento, Júlio Cézar dos Santos; Fonseca Filho, Lucilo Bioni da; Silva, Raphael Luiz Andrade; Albuquerque, Priscilla Virginio de; Pereira, Lourival Barros de Sousa Brito; Costa, Caio Alves da; Melo, Felipe Pereira de; Nascimento, Jailson Souza do; Porto, Ana Lúcia Figueiredo; Amorim, Marleyne José Afonso Accioly Lins (Pubvet, 2018)
The phosphorus (P) contained in the grains and their by-products, used in the feeding of non-ruminant animals, is largely unavailable for their absorption. Therefore, phosphorus may be 29 to 99% unavailable in ingredients of plant origin, because it is attached to the stable structure of phytic acid. It is defined by enzymes as being a group of organic substances of a normally protein nature with intra- or extracellular activity that have catalytic functions. Phytoses - Myo-inositol phosphohydrolase hexaphosphate - form a group of enzymes that catalyze the hydrolysis of phytic acid (myo-inositol hexaphosphate) and its salts (phytates), generally producing inositol, inositol monophosphate and inorganic phosphate, increasing the availability of phosphorus to the absorption. Fungi are highly efficient beings in the degradation of a wide range of substrates. The genus Aspergillus belongs to the group of filamentous fungi of great dispersion in the environment and plays an important role in the biodeterioration processes, mainly in stored and industrialized foods. Agroindustrial wastes are generated in the processing of food, fiber, leather, wood, sugar and alcohol production, and its production is generally seasonal. Fungi for selection of phytase production will be obtained from the URM collection of the Department of Mycology - UFPE. In total, 19 species of the genus Aspergillus were obtained. In the first stage of the screening the strains were replicated in the Medium Screening Phytase (MSF) to classify the possible phytase producers. MSF contains phytic acid (phytate) as its only source of carbon and phosphate. The second stage of sreening was performed with the strains that presented growth in the 1st stage. They were inoculated by the central point technique. The diameter of the colonies was measured for 96 hours. Among the 19 fungi Aspergillus spp. tested in the modified basic medium, most of the species showed growth in the medium, except the fungi A. niveus URM 2803 and A. sydowi URM 3066. A. aculeatus URM 4953 and A. janus URM 4456 showed growth of the colonies only after 24 hours of incubation. A. caespitosus URM 5182 was the microorganism that showed the most late growth (from 48 hours) in the sreening phytase medium. A. phoenicis URM 4924 stood out in the growth of the modified basic medium followed by A. niger URM 5239 with 4,800 cm in 96 hours. The present work demonstrates the potential of the filamentous fungi of the genus Aspergillus in the production of phytase for inclusion in animal feed.